Research progress on risk factors of delirium in burn patients: A narrative review - Ren, Yujie; Zhang, Yu; Luo, Jinhua; Liao, Wenqiang; Cheng, Xing; Zhan, Jianhua (Frontiers in Psychiatry, 2022)
Delirium, an acute brain dysfunction, is a common and serious complication in burn patients. The occurrence of delirium increases the difficulty of patient treatment, is associated with various adverse outcomes, and increases the burden on the patient's family. Many scholars have studied the factors that cause delirium, but the causes, pathogenesis, and treatment of delirium in burn patients have not been fully revealed. There is no effective pharmacological treatment for delirium, but active preventive measures can effectively reduce the incidence of delirium in burn patients. Therefore, it is necessary to study the relevant factors affecting the occurrence of delirium in burn patients. This study was conducted on December 20, 2021 by searching the PubMed database for a narrative review of published studies. The search strategy included keywords related to "burns," "delirium," and "risk factors." We reviewed the characteristics of delirium occurrence in burn patients and various delirium assessment tools, and summarized the risk factors for the development of delirium in burn patients in terms of personal, clinical, and environmental factors, and we found that although many risk factors act on the development of delirium in burn patients, some of them, such as clinical and environmental factors, are modifiable, suggesting that we can estimate the exposure of burn patients to risk factors by assessing their likelihood of delirium occurring and to make targeted interventions that provide a theoretical basis for the prevention and treatment of burn delirium.